Inhibition of 5-Lipoxygenase in Hepatic Stellate Cells Alleviates Liver Fibrosis - Pu, Shiyun; Li, Yanping; Liu, Qinhui; Zhang, Xu; Chen, Lei; Li, Rui; Zhang, Jinhang; Wu, Tong; Tang, Qin; Yang, Xuping; Zhang, Zijing; Huang, Ya; et al. (Frontiers in Pharmacology, 2021)
Background and purpose: Activation of hepatic stellate cells (HSC) is a central driver of liver fibrosis. 5-lipoxygenase (5-LO) is the key enzyme that catalyzes arachidonic acid to leukotrienes. In this study, we examined the role of 5-LO in HSC activation and liver fibrosis. Main methods: Culture medium was collected from quiescent and activated HSC for target metabolomics analysis. Exogenous leukotrienes were added to culture medium to explore its effect in activating HSC. Genetic ablation of 5-LO in mice was used to study its role in liver fibrosis induced by CCl4 and a methionine-choline-deficient (MCD) diet. Pharmacological inhibition of 5-LO in HSC was used to explore the effect of this enzyme in HSC activation and liver fibrosis. Key results: The secretion of LTB4 and LTC4 was increased in activated versus quiescent HSC. LTB4 and LTC4 contributed to HSC activation by activating the extracellular signal-regulated protein kinase pathway. The expression of 5-LO was increased in activated HSC and fibrotic livers of mice. Ablation of 5-LO in primary HSC inhibited both mRNA and protein expression of fibrotic genes. In vivo, ablation of 5-LO markedly ameliorated the CCl4- and MCD diet-induced liver fibrosis and liver injury. Pharmacological inhibition of 5-LO in HSC by targeted delivery of the 5-LO inhibitor zileuton suppressed HSC activation and improved CCl4- and MCD diet-induced hepatic fibrosis and liver injury. Finally, we found increased 5-LO expression in patients with non-alcoholic steatohepatitis and liver fibrosis. Conclusion: 5-LO may play a critical role in activating HSC; genetic ablation or pharmacological inhibition of 5-LO improved CCl4- and MCD diet-induced liver fibrosis.